Evaluation of Image-Guidance Strategies for Prostate Cancer. (December 2014) - Piotrowski, T.; Kaczmarek, K.; Bajon, T.; Ryczkowski, A.; Jodda, A.; Kaźmierska, J.
In this study, set-up accuracy and time consumption of different image-guidance protocols used for prostate cancer patients were compared. Set-up corrections from 60 prostate cancer patients treated on helical tomotherapy (HT) were used to simulate four types of image-guidance protocols which were based on: (i) a limited number of imaging sessions (IG-1), (ii) reduced registration tasks during daily imaging (IG-2), or (iii) and (iv) mixed methods of imaging (IG-3, IG-4). Each protocol was evaluated for three referencing scenarios based on the first fraction, first three fractions and first five fractions. Residual set-up error, the difference between the average set-up correction and the actual correction required, was used to evaluate the accuracy of each protocol. The first five fractions referencing scenario provides the highest reduction of the margins for each image-guidance protocol evaluated in this study. The first type of protocol is the shortest way to the effective correction of the systematic component of set-up error. For the second type of the protocol, the control of the residual errors is better and, as a result, the reduction of the margins is more significant than that obtained for the first one. Moreover, the second type of the protocol provides the highest accuracy of delivered dose. The result obtained for the fourth type of protocol does not decrease the calculated margins or increase their accuracy in correspondence to the no image guidance scheme. The fourth type of the protocol is not recommended as a protocol to be used to increase the conformity of the dose. The choice of the rest protocols should be validated in the context of (i) institutional practice regarding patient set-up procedure and its time consumption, (ii) acceptable balance between the amount of the dose delivered to the organ at risk and the additional imaging dose and (iii) patient anatomical conditions.